PPi analogs as inhibitors of human T-lymphotropic virus type III reverse transcriptase. - Vrang, L (1986)
Twenty-six PPi analogs were tested for inhibitory effects on human T-lymphotropic virus type III reverse transcriptase. The structural requirements for inhibition and mechanism of action of the most active inhibitors have been investigated. Foscarnet (phosphonoformic acid) was the most potent inhibitor of human T-lymphotropic virus type III reverse transcriptase with 50% inhibition at 0.5 microM. The mechanism was a noncompetitive type of inhibition of a (riboadenylic acid)n . (deoxythymidylic acid)12-18 [(rA)n(dT)12-18]-directed transcription at varied dTTP concentration. At constant substrate (dTTP) concentration and varied amounts of template, (rA)n(dT)12-18, the inhibitory action of foscarnet was of an uncompetitive type. The same pattern of inhibition was seen when the less active inhibitor carbonyldiphosphonate was studied under identical conditions. The structural requirements for inhibition of human T-lymphotropic virus type III reverse transcriptase by PPi analogs were similar to those shown by other reverse transcriptases.